ANALISIS PERENCANAAN PERSEDIAAN BATUBARA FX DENGAN METODE MATERIAL REQUIREMENT PLANNING - Muhammad Arief; Supriyadi Supriyadi (Politeknik APP Jakarta, 2017)
A company often has difficulty in controlling raw materials,it could be surplus or minus. Preventing these problem,we made a problem solving. Material needs planning is made for efficient and effective materials application in the execution of work, so the problems because of material is avoided.this research purpose is planning and controlling raw material and supplier selection by Material Requirement Planning (MRP) method. Material Requirement Planning is a method for determining materials or components which make or buy, how much it is needed and when it is needed. The result using the calculation by MRP method show Fix Period Requirement (FPR) is the best method, because the calculation of Fix Period Requirement method got the lowest total cost that is Rp.18,722,190,090, -.FPR is obtained a profit about Rp. 6.096.088.915,00 or about 25% more efficient than the method applied company.